The concept of sustainability applied by clothing companies (ModaPalavra e-periódico, 2015)
Sustainability in fashion design, is a relationship that should reflect and question because there are many parameters in the fashion system that make it unsustainable and, in particular, the jeanswear segment which is the subject matter of this research thus the this study aims to present how the concept of sustainability is employed by companies, through the subject's level of knowledge and application in the company, so the speech, as well as its applicability are reliable to sustainable criteria for both a qualitative approach, professional working in product development had their answers confronted with the literature studied during the development of the research presented in this paper, which brought an unexpected result because it showed that the concept is still approached superficially and so it is believed that it is necessary a True Discourse of what is preached in what is produced.
Keywords: sustainability; jeanswear; fashion design